Modeling and Profile Analysis of Globoidal Cam in Automatic Tool Changer - Yu Jianwu; Luo Hong; Shu Xin; Wu Yao; Wen Cheng; Hu Qifeng (Jixie chuandong)
Aiming at the problems of the work profile of globoidal cam in automatic tool changer（ ATC） is difficult to design,manufacture and both side of cam groove meshing with the roller in indexing period,taking the globoidal cam of a certain machining center as example,the motion and position relationship between globoidal cam and indexing plate are analyzed,the mathematical equation of globoidal cam contour surface is derived and modified. By using the segment modeling method,the cam profile curve groups in both indexing period and dwell period are created in Pro/E software. By the physical modeling of line and surface,the accurate 3D solid model of the globoidal cam is established. After globoidal cam profile performance analysis and machining practice,the designed globoidal cam model is verified to meet the design and machining requirements,which provides technical support for improving its finish grinding accuracy.